PERAN ORANGTUA DALAM MENCIPTAKAN LINGKUNGAN POSITIF BAGI ANAK TUNARUNGU DAN TUNAWICARA BERPRESTASI DI SEKOLAH INKLUSI: ANALISIS KUALITATIF DESKRIPTIF - Adela Sabira; Deanisa Niki; Dina Santika; Edwita Zaulia; Harum Sari; Nabila Chairunnisa; Rafi Haykal; Riska Amalia (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to analyze the role of parents in creating a positive environment for high-achieving deaf students in inclusive sixth-grade classrooms. A descriptive qualitative method was used, with data collection techniques including in-depth interviews, participatory observation, and documentation. The results show that parents play a central role in providing emotional support, motivation, and facilitating effective communication, enabling deaf children to optimally develop their academic and social potential. Furthermore, collaboration between parents and teachers in inclusive schools is also a crucial factor in fostering an inclusive and supportive learning environment. The study also reveals various challenges faced by parents, such as limited resources and social stigma, as well as the strategies they use to overcome these obstacles. These findings provide a comprehensive picture of the importance of empowering parents as key partners in inclusive education. This research is expected to serve as a foundation for the development of policies and programs that support the success of deaf students in inclusive schools.